Strengthening Environmental Awareness: Pandawara Group's TikTok Account as a Source of Inspiration - Nizar Risqy Andhreawan; Ardiyanto Wardhana (Jogjakarta Communication Conference (JCC), 2024)
This study aims to determine the impact of content uploaded by Pandawara Group on TikTok social media on environmental awareness. The research method used is an observational approach that focuses on direct observation of user responses and interactions before and after viewing content from Pandawara Group. In making these observations, researchers paid attention to various activities carried out by users, including giving likes, comments, and sharing content, as well as changes in behavior related to environmental awareness after they were exposed to the content. The results of the observation showed an increase in user participation after viewing Pandawara Group content. TikTok social media users tend to be more active in providing positive responses such as giving likes, leaving comments, and sharing content with their friends. In addition, there is a positive change in users' behavior regarding environmental awareness, which is reflected in their actions after viewing the content. The analysis and discussion in this study link the findings obtained with previous related literature on social media and environmental awareness. The findings also have relevant implications in the context of further research on the role of social media in strengthening environmental awareness and encouraging positive actions in protecting the environment. Thus, this study is expected to make a significant contribution to our understanding of the influence of social media, particularly TikTok, in shaping environmental awareness and encouraging environmental stewardship behavior.